Centralna naselja v Sloveniji in njihova vplivna območja v letu 1999 - Cigale, Dejan (Geografski vestnik, 2002)
The aim of the research was to analyses the network of central places in Slovenia and their spheres of influence. It was also an attempt at the identification of changes in the network of central places in the past decade.The necessary data were obtained with the help of the questionnaire survey. In order to get information about the provision of central places withdifferent services extensive statistical and other data sources were used. We have concentrated our attention on the higher order central places network, while the lower order central places haven`t been differentiated morein detail. It has been possible to distinguish 2 macro regional centres, 17 mezzo regional centres and 79 micro regional centres. Besides that there are also numerous smaller centres on the lower hierarchical levels.
Keywords: naselja; geografija naselij; centralna naselja; omrežja naselij; Slovenia; Slovenija